2018
DOI: 10.1634/theoncologist.2017-0451
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation and First-Round Results of a Community-Based Colorectal Cancer Screening Program in Shanghai, China

Abstract: There is good evidence of the benefits of early detection of cancer and removal of adenomas in asymptomatic individuals; however, the widespread implementation of colorectal screening programs is resource‐dependent. Such programs have been widely implemented in high‐income regions and countries in North America, Europe, Japan, and South Korea, but such programs are few in low and middle‐income countries [35]. This article describes the implementation of a comprehensive approach to colorectal cancer screening i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
84
4
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(99 citation statements)
references
References 33 publications
5
84
4
3
Order By: Relevance
“…Colonoscopy adherence in the population with positive preliminary screening results determines the effectiveness of CRC screening and early diagnosis. However, unsatisfactory levels of colonoscopy adherence have been reported in some studies, and even lower adherence has been reported in China . From 2012 to 2013, data from 14 cities in China showed that among high‐risk urban residents with positive results on preliminary screening with questionnaires, only 33.25% underwent colonoscopy .…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy adherence in the population with positive preliminary screening results determines the effectiveness of CRC screening and early diagnosis. However, unsatisfactory levels of colonoscopy adherence have been reported in some studies, and even lower adherence has been reported in China . From 2012 to 2013, data from 14 cities in China showed that among high‐risk urban residents with positive results on preliminary screening with questionnaires, only 33.25% underwent colonoscopy .…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of The Oncologist , Gong, Peng, and colleagues from the Shanghai Municipal Center for Disease Control and Prevention (Shanghai CDC) report on the planning, implementation, and outcomes of the first round of a community‐based colorectal cancer program in Shanghai, People's Republic of China . The report illustrates the importance of fundamental components of public health surveillance and health service delivery systems needed to support a community‐based screening program.…”
mentioning
confidence: 99%
“…Data from the periodic population‐based risk factor surveillance survey were useful to show low reported use of colorectal cancer screening modalities in the general population. The Shanghai government further invested in a dedicated, web‐based colorectal cancer screening registry and information management system , linked to cancer outcomes in the vital and cancer registries via unique personal identifying number. These data resources enable the Shanghai CDC to optimally evaluate the costs, operations, and impact of the screening program in reducing colorectal cancer mortality and morbidity in the defined target population.…”
mentioning
confidence: 99%
See 2 more Smart Citations